2023
DOI: 10.3389/fonc.2023.1104659
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of molecular alterations identified by high throughput sequencing in patients with advanced solid tumors in treatment failure: Real-world data from a French hospital

Abstract: BackgroundIn the context of personalized medicine, screening patients to identify targetable molecular alterations is essential for therapeutic decisions such as inclusion in clinical trials, early access to therapies, or compassionate treatment. The objective of this study was to determine the real-world impact of routine incorporation of FoundationOne analysis in cancers with a poor prognosis and limited treatment options, or in those progressing after at least one course of standard therapy.MethodsA Foundat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The median age of the patients included in our study was 60.5 (range 27-82) years, which is similar to the median age of the population reported in different studies that analysed solid tumour samples with the Foundation Medicine ® platform [17][18][19][20]. A total of 72 samples were processed for the identification of genomic alterations, and data were obtained for 67 samples, corresponding to a success rate of 93.1%.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The median age of the patients included in our study was 60.5 (range 27-82) years, which is similar to the median age of the population reported in different studies that analysed solid tumour samples with the Foundation Medicine ® platform [17][18][19][20]. A total of 72 samples were processed for the identification of genomic alterations, and data were obtained for 67 samples, corresponding to a success rate of 93.1%.…”
Section: Discussionsupporting
confidence: 54%
“…Despite the presented data and the potential benefits that patients can gain following the development of precision oncology, most of the genomic alterations identified in this study have no direct match with currently approved drugs, as reported in other large series using the same test [17][18][19]. One such example in this study is the cancers of unknown primary, which presented KRAS alterations.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, a Hawthorne effect may be in play; patients who are aware that they are being surveyed may (consciously or unconsciously) overestimate their compliance rates [41]. Recruitment bias may be in play; many patients had brain tumors (our center has expertise in this eld) [18,42]. However, unlike other studies, we did not select particular types of tumors and the QR code was available to all cancer patients.…”
Section: Discussionmentioning
confidence: 99%